Failure of non-cultured melanocyte-keratinocyte transplantation in periungual vitiligo: A case report - Norah Alsubait; Sanjeev Mulekar; Ahmed Al Issa (Wolters Kluwer Medknow Publications, 2015)
Background: Vitiligo is a common pigmentary skin disorder, affecting 0.5-1% of world population. It is one of the psychologically devastating skin disorders, which have different medical and surgical modalities of treatment. Objective: To report the failure of non-cultured melanocyte-keratinocyte transplantation in periungual vitiligo. Method: The method used was introduced by Gauthier and Surleve-Bazeille, modified by Olsson and Juhlin, and recently by Mulekar. A shaved biopsy skin sample of approximately one-fifth the size of the recipient area was used. Skin sample is incubated; cells mechanically separated using trypsin-EDTA solution, and then centrifuged to prepare a suspension. The suspension is then applied to dermabraded depigmented skin area and collagen dressing was used to keep it in place. Results: Treated lesions on the right hand of female with stable periungual vitiligo showed very poor repigmentation (less than 10%) with only very small new brown spots. Conclusion: Acral vitiligo is one of the difficult-to-treat areas, and further studies are required to explain the variable outcomes of non-cultured melanocyte-keratinocyte transplantation treatment of clinically stable acral vitiligo patients.